Development of Digital Mathematics Teaching Materials Based on a Self-Regulated Learning Approach to Increase the Creativity of Jakarta Teachers - Flavia Aurelia Hidajat (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The creativity of teachers in developing digital mathematics teaching materials is required to increase students' understanding independently in online learning. A good learning strategy to increase creativity and independent learning is self-regulated learning. This community service training aims to increase the creativity of Jakarta teachers in developing teaching materials for digital mathematics learning based on a self-regulated learning approach. Twenty-three high school teachers in Jakarta attended the training. The stages consist of pre-training, training process, and post-training. The results of this community service training. The results show that: The teachers understand the material about the systematic development of digital mathematical teaching materials; Training provides clear information; The output of the training can help the learning of teachers; Teachers' creativity is increasing by making mathematics digital teaching material based on self-regulated learning Approach as the output of this training.